S63 Baseline Asthma Control and Severity Influences the Outcome of Virus-Induced Asthma Exacerbations. (19th November 2012) - Jackson, DJ; Trujillo-Torralbo, M; Footitt, J; Mallia, P; Kon, OM; Hansel, TT; Johnston, SL
Abstract : Background: Rhinovirus (RV) infection is the most common cause of asthma exacerbations (AE). Mechanisms underlying this remain poorly understood. A human model of experimental RV induced AE has been developed however published studies have only recruited subjects with mild, well-controlled asthma naive to inhaled corticosteroid (ICS) therapy. The influence of asthma severity and baseline control on outcome remains unknown. For these studies to be more representative of those who experience virus-induced AE there is a need to establish the safety of using this model in subjects with moderate, poorly-controlled asthma and to investigate clinical outcomes. Method: 48 adults - 14 healthy, 14 mild asthmatic, and 18 moderate asthmatic (defined by GINA) were recruited and inoculated nasally with RV-16. Daily symptom scores and spirometry were recorded throughout the study. Asthma control at baseline was recorded using the ACQ. Nasal lavage (NL) for viral shedding was performed on days 0, 2, 3, 4, 5, 7, 10. Clinical infection was confirmed by demonstration of RV16 RNA by RT-PCR in NL and/or serum titre of RV-16 specific antibodies greater than 1:4 on d42. Results: 11/14 healthy, 11/14 mild asthmatic and 17/18 moderate asthmatic volunteers met criteria for infection. Both groups of asthmatics developed greater lower respiratory symptoms, falls in FEV1, and airway hyper-responsiveness (AHR) compared to healthy volunteers (all P =<0.01). These changes were significantly greater in the moderate asthmatics than in the mild asthmatics ( P =<0.05). Poorly-controlled asthmatics experienced greater chest symptoms ( P =<0.01) and RV-induced falls in lung function ( P =<0.05) compared to subjects with well-controlled asthma. Conclusion: RV infection results in more severe chest symptoms and falls in lung function in moderate asthma than in mild asthma. Within the moderate group the poorly-controlled asthmatics experienced the most severe exacerbations. This occurred despite therapy with ICS. This is the first study to experimentally inoculate both moderate, poorly-controlled and milder well-controlled asthmatics. Both severity and baseline control appear to influence the outcome of virus-induced AE. Measures to improve control will significantly reduce the likelihood of a severe virus-induced AE and lessen the healthcare costs associated with them.